2013
DOI: 10.1073/pnas.1311967110
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte control of synaptic NMDA receptors contributes to the progressive development of temporal lobe epilepsy

Abstract: Astrocytes modulate neuronal activity, synaptic transmission, and behavior by releasing chemical transmitters in a process termed gliotransmission. Whether this process impacts epilepsy in vivo is not known. We show that genetic impairment of transmitter release from astrocytes by the expression of a glial dominantnegative SNARE domain in mice reduced epileptiform activity in situ, delayed seizure onset after pilocarpine-induced status epilepticus, and attenuated subsequent progressive increase in seizure freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 30 publications
5
66
0
Order By: Relevance
“…Hippocampal sclerosis is commonly observed in patients with temporal lobe epilepsy (TLE). 12 Clasadonte et al 13 demonstrated in a mouse pilocarpine model of TLE that hyperfunction of NMDARs at the CA1 hippocampal synapses causes hippocampal sclerosis and that astrocytes play an important role in controlling NMDARs by releasing chemical transmitters in a process termed gliotransmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal sclerosis is commonly observed in patients with temporal lobe epilepsy (TLE). 12 Clasadonte et al 13 demonstrated in a mouse pilocarpine model of TLE that hyperfunction of NMDARs at the CA1 hippocampal synapses causes hippocampal sclerosis and that astrocytes play an important role in controlling NMDARs by releasing chemical transmitters in a process termed gliotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is an important brain region involved in neurological disorders such as AD, schizophrenia, and epilepsy. [10][11][12][13] Therefore, we need to develop an assay system that uses human hippocampal neurons so that we can obtain a detailed understanding of the molecular mechanisms underlying these diseases and discover novel drugs for treating them.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these studies, LTP was triggered by high-frequency stimulation (HFS), and the effects of genetic or pharmacological manipulation of astrocytes assessed in parallel. In the first study of astrocytes in LTP, dominant-negative inhibition of vesicular release (soluble NSF attachment protein receptors [SNARE]) under the astrocyte-specific promoter, glial fibrillary acidic protein (GFAP), lowered baseline adenosine concentration (Pascual et al 2005), which leads to a long-term change in postsynaptic NMDAR trafficking (Clasadonte et al 2013), and, as a consequence, leads to a change in modulation of the magnitude of NMDAR-dependent LTP. In another study, Dserine release from astrocytes was shown to be critical for NMDAR-dependent LTP (Henneberger et al 2010).…”
Section: Long-term Changes In Neural Network and The Role Of Astrocytesmentioning
confidence: 99%
“…In recent years, accumulating data have suggested that astrocyte dysfunction contributes to the development of epilepsy, including seizure occurrence, neuronal damage, and behavioral impairment [15][16][17]. Excessive or prolonged reactive astrogliosis is a recognized response to seizures and a potential contributor to mechanisms of epileptogenesis [18,19].…”
Section: Introductionmentioning
confidence: 99%